Innovative pedagogical practices in nursing education - Nurumal, Mohd. Said (2020)
Innovative pedagogy has been studied in a variety discipline. Often poorly understood and can be confused sometimes with related: change, invention, design, creativity. Derived from Latin root: defined as “making changes to something established by introducing something new”.